2014
DOI: 10.1016/j.jconrel.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug delivery to intact and porated skin by coherent Raman scattering and fluorescence microscopies

Abstract: Stimulated Raman scattering microscopy was used to assess the permeation of topically applied drugs and formulation excipients into porcine skin. This chemically selective technique generates high-resolution 3D images, from which semi-quantitative information may be elucidated. Ibuprofen, applied as a close-to-saturated solution in propylene glycol, was directly observed to crystallise in/on the skin, as the co-solvent permeated more rapidly, resulting in precipitation of the drug. Coherent Raman scattering mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 14 publications
0
59
0
Order By: Relevance
“…Several reports have shown the detection of drug crystals on mammalian skin but little is known about how the phenomenon actually happens in the skin [5,6]. This study explored the combined abilities of (i) ATR-FTIR spectroscopy to detect drug crystals in skin samples and (ii) multivariate data analysis for differentiation of spectral characteristics descriptive of the physical state of the model drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have shown the detection of drug crystals on mammalian skin but little is known about how the phenomenon actually happens in the skin [5,6]. This study explored the combined abilities of (i) ATR-FTIR spectroscopy to detect drug crystals in skin samples and (ii) multivariate data analysis for differentiation of spectral characteristics descriptive of the physical state of the model drug.…”
Section: Discussionmentioning
confidence: 99%
“…Saar et al [5] showed the formation of ibuprofen crystals on excised mouse skin using simulated Raman scattering (SRS) imaging, following application of a solution of deuterated ibuprofen in propylene glycol (PG). More recently, Belsey et al [6] observed large ibuprofen crystals on porcine skin 30 min post application of a saturated solution of ibuprofen in PG using the same imaging technique. However, actual location of crystals in the skin remains a limitation of SRS imaging as is the apparent requirement for deuteration of the active of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, bilayers at different depths will be exposed to different concentrations of the permeating molecules and determining the effective concentrations of each of the formulation ingredients in the SC is extremely challenging. Although recent progress has been made using Raman scattering microscopy 3 , only semi-quantitative information may be elucidated at the current time. Experiments reported in the literature have investigated the permeation of selected compounds in EtOH-containing mixtures from very low concentrations of EtOH up to pure EtOH, for examples see Ref 4 .…”
Section: Choice Of Model Systemsmentioning
confidence: 99%
“…When working with dermatological applications of nanoparticles, therefore, it would be useful to have a method for imaging fluorescence that (1) was free of interfering background signal, (2) operated on a macro (in millimeters) viewing scale, rather than either a micro or in vivo scale, and (3) also able to quantify the signal intensity. Recent methods reported include techniques, such as Raman spectroscopy, which has been used to quantify the penetration of nanoparticles into skin at micro-scale depths [13,14].…”
Section: Introductionmentioning
confidence: 99%